Dual Strategy: Female Oversight and Financial Expertise Curb Audit Delay in Complex Firms - Putri, Anisa Maylana; Ricky, Ricky (Journal of Business and Economics Research (JBE), 2025)
Audit delays are a significant issue in financial reporting because they can reduce the reliability of information and create uncertainty for investors. This study aims to understand the impact of operational complexity, audit committee gender, and CEO financial expertise on audit delays in mining companies listed on the Indonesia Stock Exchange during the 2021-2023 period. This study uses a quantitative research design utilizing secondary data compiled from corporate annual reports. Using purposive sampling, 52 companies were selected, contributing 156 observations, and data processing was performed through multiple linear regression to evaluate the relationship between variables. The results show that operational complexity and CEO financial expertise do not have a significant effect on audit delays. Conversely, audit committee gender has a significant negative effect, meaning that the presence of women on audit committees can accelerate the completion of the audit process. These findings support corporate governance theory, which asserts that gender diversity can improve the effectiveness of oversight and regulatory compliance, thereby reducing the potential for audit delays. Furthermore, the results of this study contribute practically to the interests of regulators and companies in promoting timely financial reporting.